2017
DOI: 10.1111/all.13125
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of mobile phone technology in allergic rhinitis in European countries: the MASK‐rhinitis study

Abstract: Background: The use of Apps running on smartphones and tablets profoundly affects medicine. The MASK-rhinitis (MACVIA-ARIA Sentinel NetworK for allergic rhinitis) App (Allergy Diary) assesses allergic rhinitis symptoms, disease control and impact on patients' lives. It is freely available in 20 countries (iOS and Android platforms). Aims: To assess in a pilot study whether (i) Allergy Diary users were able to properly provide baseline characteristics (ii) simple phenotypic characteristics based upon data captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
142
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(150 citation statements)
references
References 41 publications
1
142
0
7
Order By: Relevance
“…As the magnitude of correlation coefficients is affected by the range of scores included in the sample, increasing as the range of scores increases, ICCs were calculated separately for VAS scores above and below 50 mm; The sensitivity . It was evaluated by the Cronbach’ alpha coefficient, the difference of measures and the standard deviation in the VAS, for those users logging into the app more than once per day, but self‐assessing their symptoms with a interval of less than 3 hours (thus, eliminating bias related to possible changes in allergen exposure and/or drug intake). The external validity having already been described in a previous paper …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the magnitude of correlation coefficients is affected by the range of scores included in the sample, increasing as the range of scores increases, ICCs were calculated separately for VAS scores above and below 50 mm; The sensitivity . It was evaluated by the Cronbach’ alpha coefficient, the difference of measures and the standard deviation in the VAS, for those users logging into the app more than once per day, but self‐assessing their symptoms with a interval of less than 3 hours (thus, eliminating bias related to possible changes in allergen exposure and/or drug intake). The external validity having already been described in a previous paper …”
Section: Methodsmentioning
confidence: 99%
“…Users may self‐evaluate their AR control by a VAS that appears on their phone screen. Preliminary data showed that the app enables baseline and simple phenotypic characteristics collection …”
Section: Introductionmentioning
confidence: 99%
“…These findings emphasize the need for dissemination of readily accessible guidelines and practice recommendations to GP, who are usually not trained in depth regarding chronic management of these respiratory diseases. For example, in Europe there are several initiatives to establish accessible treatment algorithms for practitioners, such as for AR [38, 40], and to improve patient education and communication with physicians using technology to monitor AR symptoms [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Bununla ilgili 5000 kullanıcının (%9'u 60 yaşın üzerinde) katıldığı pilot çalışma, bu soruların kolaylıkla yanıt-landığını ve rinit hastalarının sınıflanmasına yardımcı olduğunu göstermiştir (28).…”
Section: • Anketlerunclassified